Synthesis of curvulone B and allahabadolactone, and the development of a diastereoselective Tsuji-Trost cyclisation - Wang, Kongchen (2017)
The first chapter describes the synthesis of curvulone B featuring a strategy of cross metathesis and oxa-Michael addition in the construction of the desired cis-THP ring. This strategy is one of the most effective tools in the synthesis of THP rings containing natural products. o-Chlorobenzyl ether was developed as a new protecting group for alcohols and proved to be a reliable protecting group under Lewis acidic condition. Chapter two describes the development of a diastereoselective Tsuji-Trost cyclisation. This method was applied in the synthesis of multi-substituent six-membered rings. Chapter three describes the total synthesis of allahabadolactone A though a route featuring alkyne hydroboration, stereospecific Suzuki coupling and an intramolecular Diels-Alder (IMDA) reaction. This work confirmed the superiority of the aldehyde as an electron withdrawing group for the IMDA reaction and, for the first time, demonstrated the unsuitability of the alkyne substituent in the IMDA reaction. Also, the absolute stereochemistry of allahabadolactone A was confirmed by the synthesis. Meanwhile, a new Rh catalyst was prepared with (2-furyl)3P ligand, which could be utilized efficiently in the hydroboration of terminal alkynes.